Mass and EPR Spectra of Zinc(II) Cyclotriphosphazenide - SINGH, NEETU; JADON, S.P.S. (Asian Journal of Chemistry, 2010)
Complex of Zn2+ with hexahydrocyclotriphosphazene was synthesized. The complex was characterized with the help of mass, IR and EPR spectra, assigning its molecular formula as Zn(N3P3H4)3 as tridentated coordinated complex.